Compromised base excision repair pathway in Mycobacterium tuberculosis imparts superior adaptability in the host. - Saba Naz; Shruti Dabral; Sathya Narayanan Nagarajan; Divya Arora; Lakshya Veer Singh; Pradeep Kumar; Yogendra Singh; Dhiraj Kumar; Umesh Varshney; Vinay Kumar Nandicoori (PLoS Pathogens)
Tuberculosis caused by Mycobacterium tuberculosis (Mtb) is a significant public health concern, exacerbated by the emergence of drug-resistant TB. To combat the host's dynamic environment, Mtb encodes multiple DNA repair enzymes that play a critical role in maintaining genomic integrity. Mtb possesses a GC-rich genome, rendering it highly susceptible to cytosine deaminations, resulting in the occurrence of uracils in the DNA. UDGs encoded by ung and udgB initiate the repair; hence we investigated the biological impact of deleting UDGs in the adaptation of pathogen. We generated gene replacement mutants of uracil DNA glycosylases, individually (RvΔung, RvΔudgB) or together (RvΔdKO). The double KO mutant, RvΔdKO exhibited remarkably higher spontaneous mutation rate, in the presence of antibiotics. Interestingly, RvΔdKO showed higher survival rates in guinea pigs and accumulated large number of SNPs as revealed by whole-genome sequence analysis. Competition assays revealed the superior fitness of RvΔdKO over Rv, both in ex vivo and in vivo conditions. We propose that compromised DNA repair results in the accumulation of mutations, and a subset of these drives adaptation in the host. Importantly, this property allowed us to utilize RvΔdKO for the facile identification of drug targets.